Enhancing Students’ Writing Skill by Using Collaborative Writing At The Third Semester Students of The English Study Program Of The Muhammadiyah University Of Bengkulu - Eki Saputra (Edelweiss : Journal Of Innovation In Educational Research, 2024)
This study was aimed to investigate how collaborative writing improved students’ writing skill. The research subject was class A of third semester students at Muhammadiyah University of Bengkulu. This research was qualitative research which focused on classroom action research (CAR). The data were collected from field note, observation checklist, students’ final draft analysis and by recording the whole process of classroom action research, either before or during the implementation of the actions. The finding of the research indicated: (1)The collaborative writing had been effectively improved students’ writing skill particularly in writing anessay. (2) The collaborative writing is very feasible to be implemented in teaching writing. Finally, the reseacher suggested that there should be some other reseachers conducting some researches about the collaborative technique to enhance students’ other language skills.